Competitiveness and cultural dimensions: an analysis of European Union and Unasur - Barcelos, Renato Hübner; Chevarria, Diego Gonzales; Pantoja, Felipe Cohen Ferreira; Yamim, Amanda Pruski; Nique, Walter Meucci (Revista de Administração da UFSM, 2017)
The twentieth century has witnessed the formation of various alliances and trade blocs among nations. These alliances have often been more based on geographic and economic proximity than on cultural similarity. However, culture might be an essential factor in the explanation of some discrepancies between countries of the same trade bloc, such as the competitiveness indicators. Therefore, this study aims to analyze the relationship between national culture and the competitiveness index of nations, in the context of UNASUR and the European Union. By means of correlation analysis and clustering (K-means), it was possible to identify a strong correlation between the dimensions of national culture proposed by Hofstede and the nations’ competitiveness indicators. Most countries in South America have great similarities in cultural dimensions and form a single cluster, while countries in the European Union have higher distinctions and are separated into two distinct clusters. Finally, MANOVA tests applied on the clusters reveal that the differences found in relation to the dimensions of national culture are also reflected in the market efficiency indicators of the countries. Thus, the results taken together suggest the need to consider the impact exerted by the culture on the competitiveness of nations.